Estratégias de redução dos resíduos sólidos domiciliares a serem dispostos em aterros sanitários: redução na fonte, coleta seletiva e metanização - Oliveira, Mariana Moreira de (2022)
Household solid waste (HSW) is a representative fraction of municipal solid waste. According to the National Policy for Solid Waste, the management of solid waste must obey the following hierarchy: non-generation, reduction, reuse, recycling, treatment of solid waste and environmentally adequate final disposal of the refusal. Thus, the present research aimed to analyze the effect of HSW reduction strategies by means of its minimization at the source and by the specific treatment of the recyclable dry fraction (RFHWS) and an easily biodegradable organic fraction (OFHSW) in order to reduce the amount of waste sent to landfills and the impacts involved. To measure such strategies, the HSW of four vertical residential condominiums was analyzed (A, B, C and D). First, the generation rate and composition of HSW were analyzed, then awareness campaigns were conducted with the residents and the most adopted minimization measures were analyzed. To measure the effect of awareness-raising on reducing the generation of HSW, the rate of generation of this waste before and after the awareness-raising activity was determined. Measurement of the effects of recycling on RFHSW was performed by quantifying this fraction, separated by the implemented selective collection. For the OFHSW, initially a pre-treatment study of the OFHSW was carried out before submitting them to methanization and later the characterization of this fraction of the condominiums was performed. Finally, management scenarios were determined. Regarding the HSW parameters, distinct values were found for the rate of HSW generation in the analyzed periods, of 0.526 (I), 0.491 (II) and 0.470 (III) kg.hab-1.day-1, and it was observed the predominance of the OFHSW (59%), which together with the RFHSW (21%), totals 80% of usable waste. A 16% reduction in the generation rate was identified after awareness-raising of the population. Among the minimization measures, the most adopted was avoiding the use of packaging and wastage, and donating/selling unnecessary objects. Concerning the RFHSW, an average separation rate of 0.07 kg.hab-1.day-1 was obtained and the separation of 19% and 14% of the HSW in the dry collector was observed for condominiums C and D, respectively, representing a participation rate of 82% and 57% in these condominiums, respectively. Among the obstacles pointed out by the residents, the difficulty in changing their own habits was the most observed. About the OFHSW, the previous study pointed out that the analyzed fraction presented suitable characteristics for treatment through anaerobic digestion, with an average BMP of 407.2 mL.g-1VS; and when submitted to pre-treatment, it was observed that the addition of water at the rate of 10g water.g-1TS of this waste, increased the production of methane in the liquid fraction. The OFHSW of the condominiums also showed similar characteristics. It was observed that the treatment of the entire RFHSW and OFHSW is capable of potentially reducing 87% and 86% of the waste sent to the landfill, respectively, by the condominiums as a whole and the municipality of João Pessoa. In this sense, the results presented can help the municipality's public agencies to increase the scope of selective collection in João Pessoa, aiming at both the treatment of RFHSW and OFHSW.